Entrepreneurship and Creative Destruction - Cathleen Johnson; Robert Lusch; David Schmidtz (Business Ethics and Leadership)
The study deals with reasons for the inefficient operation of the business sector in the economy through the analysis of the relationship between disruptive innovation and creative destruction. The research is carried out in the following logical sequence: the first stage presents William Baumol’s hypothesis about why entrepreneurship makes some societies richer and some poorer. There is entrepreneurship in every society, Baumol says, but background circumstances vary, so that entrepreneurship can be productive, but depending on circumstances it also can be unproductive, or even downright destructive. The second stage substantiates the relationship between entrepreneurship, disruptive innovation, and creative destruction; the third stage investigates the role of entrepreneurs in society as integrators of resources and as managers of risk; the last stage defines possible problems in how the business sector functions in society. The study is based on the generalized works shown in the book “Commercial Society” and considers deep but not obvious links between ethics, economics and entrepreneurship. In this work,the ethical question is how people have to live in order to make the world a better place. The economic question is what kind of society makes people willing and able to use their talents in ways that are good for themselves and for their communities. The entrepreneurial question is how people can bring services to the marketplace that can take a community to the next level of prosperity? The article offers tools for evaluating the interconnected effect of three business components: ethics, economics and entrepreneurship. In the framework of entrepreneurship, the authors assess the central role of honesty not only in earning a community’s trust, but also in accurate self-assessment. For a corporation to flourish, its key decision makers must be honest with themselves and each other about when their products, supply chains, or marketing strategies are not good enough and need to change. The role of the accountant in obtaining and processing information is likewise substantiated. Accounting calls for sophisticated forms of honesty and integrity: sorting through volumes of data so as to present a truth about a company’s cash flow that will not mislead the client.